ChemInform Abstract: Highly Fluorescent, π‐Extended Indenopyrido[2, 1‐a]isoindolone Derivatives Prepared by a Palladium‐Catalyzed Cascade Reaction. Issue 38 (30th August 2013) - Chamas, Zein el abidine; Marchi, Enrico; Modelli, Alberto; Fort, Yves; Ceroni, Paola; Mamane, Victor
Abstract A new series of the title compounds is prepared and the photophysical properties in CH2Cl2 are determined.